Father Involvement in Parenting and Its Powerful Link to Prosocial Behavior in Early Childhood - Wita, Arsyizahma; Villanueva, Andres (CV Berkah Syahdin Trust, 2025)
Purpose – This study investigates the relationship between father involvement in parenting and the prosocial behavior of preschool children in Tanah Datar District. The low prosocial behaviors, such as helping, sharing, cooperating, and providing comfort to others, prompted the exploration of fatherly involvement as a possible influencing factor. Design/methods/approach – A quantitative correlational approach was employed, with a sample of 194 children selected from a population of 1,128 using probability stratified cluster random sampling. Data were collected through Likert-scale questionnaires and analyzed using the product-moment correlation method with SPSS. Findings – The results reveal a significant and strong positive correlation of 0.866 between father involvement in parenting and prosocial behavior in early childhood. This indicates that higher levels of father involvement are associated with greater prosocial behavior in children. Research implications/limitations – The study's limitations include its cross-sectional design, which restricts causal inferences, and the reliance on self-reported data, which could introduce bias. Future research could expand on these findings by using longitudinal designs to better establish causality. Originality/value – This research contributes valuable insights into the impact of father involvement on children's social development, particularly in a rural Indonesian context. The findings highlight the importance of fatherly engagement for fostering prosocial behaviors in early childhood, suggesting areas for future intervention and policy development.